STUDY ON QUALITY OF INDIVIDUALS' LIFE OF XXI CENTURY THROUGH WORK - Diana-Elena, SERB; Georgeta, GOGEANU (ANDRONACHE) (Strategii Manageriale, 2014)
Given that there have been written a number of books, numerous papers, theses that treat the subject work in people's lives, this article aims to bring added value by identifying the extent that it contributes to improving the quality of individuals' life. During the two parts of the article (state of the art and theoretical) the article focuses on relevant issues which have national and international literature sources, but also international websites specialized in work analysis. The data, on I have completed the practical part of this article, comes from a site specialized in the study of quality of people's live ,,Word Values Survey". The theoretical part is a office marketing research focused on the analysis of secondary sources. The working hypothesis of this article assumes that work is one of the determinants of people's life quality, because it determines the individual's moral and financial satisfaction, and through economic situation the individual can lead a better life. The research is actually a comparative analysis based on a survey among Romanians and Ukrainians to identify how they perceive some aspects related to work. TWord Values SurveyT has an application and, as a result of the orders, it has provided me information from surveys applied, whereon I analyzed and interpreted in my own way, but objectively. The research reveals that there is a difference of opinion between the two countries on relevant issues related to work.